CHALLENGES AND UTILIZING RESULTS EFFECTIVELY IN INTERNA THE TIONAL EVALUATION ADDRESSING PROCESSES - Sayfiddinova Ruxsora; Ahmedov Azimjon (TADQIQOTLAR.UZ, 2024)
The rapid and profound transformations occurring in our country in recent years necessitate a re-evaluation of all aspects of human life, viewed through the lens of globalization  and  integration,  demanding  new  perspectives,  understandings,  and approaches.  Globalization  and  integration  processes  are  currently  evident  in  every sector worldwide. Education, in particular, has become a priority area of state policy, with reforms underway to develop education based on innovative ideas. Societal and life changes demand a new innovative approach to the education system,  accelerating  the  integration  of  education,  science,  and  production. Consequently,  the  application  of  new  innovations  to  the  educational  process  has become a pressing issue.